f(x) + g(x) = 9x + 4 If f(x) = 4x – 3, find g(x). A g(x) = 13x + 1 B. 8(X) = 5x + 1 C. g(x) = 5x + 7 D. g(x)

Question

f(x) + g(x) = 9x + 4
If f(x) = 4x – 3, find g(x).
A g(x) = 13x + 1
B. 8(X) = 5x + 1
C. g(x) = 5x + 7
D. g(x) = -13x – 7

in progress 0
Gabriella 3 days 2021-09-11T21:41:10+00:00 2 Answers 0

Answers ( )

    0
    2021-09-11T21:42:23+00:00

    Step-by-step explanation:idk

    0
    2021-09-11T21:43:05+00:00

    Answer:

    C. g(x) = 5x + 7

    Step-by-step explanation:

    f(x) + g(x) = 9x + 4

    g(x) = (9x + 4) – f(x)

    g(x) = 9x + 4 – 4x + 3

    g(x) = 9x – 4x + 4 + 3

    g(x) = 5x + 7

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )